Hospital-Based Surveillance of Carbapenem-Resistant Bacterial Infections in A Tertiary Care Center of Chattogram (IAHS Medical Journal, 2026)
Background: The global rise of Carbapenem-Resistant Organisms (CROs) represents a significant challenge to modern healthcare, limiting treatment options, increasing morbidity and mortality among hospitalized patients. These multidrug-resistant pathogens, particularly among Enterobacteriaceae, Pseudomonas and Acinetobacter species, have emerged as critical nosocomial threats in tertiary care settings. Early detection and continuous surveillance are essential to guide infection control practices and optimize antimicrobial management. This study aimed to determine the occurence, phenotypic characteristics, and antimicrobial susceptibility patterns of carbapenem-resistant bacterial isolates in a tertiary care hospital, thereby assessing the local epidemiology and informing clinical management strategies.Materials and methods: A cross-sectional hospital-based study was conducted for 6 months from January to June 2025 in the Department of Microbiology at Institute of Applied Health Sciences (IAHS) targeting clinical specimens from patients admitted to various departments. Isolates were identified using standard microbiological techniques and carbapenem resistance was screened using disk diffusion method. Antimicrobial susceptibility profiles were determined according to CLSI (Clinical and Laboratory Standard Institutes) guidelines.Results: Over the 6-month period (January-June 2025) 721 clinical specimens were examined, yielding 184 significant bacterial isolates. The study population had a mean age of 35.0 ± 21.34 years (IQR 20.5–51.0 years). Urine constituted the majority of specimens (140/184, 76.1%) followed by wound swab/pus (30/184, 16.3%) and sputum (14/184, 7.6%). Most isolates originated from the Outpatient Department (n=94), Medicine Ward (n=33) and Pediatrics Ward (n=22). Escherichia coli predominated in urine (50.7%) Klebsiella spp. in sputum (78.6%) and Pseudomonas spp. in wound/pus samples (37.5%). Out of 142 isolates tested for carbapenem resistant, the highest carbapenem resistance was observed in Proteus spp. and E. coli from wound swabs (100%) and Pseudomonas spp. from sputum (100%) and urine (75%). Klebsiella spp. showed moderate resistance across all sample types. Carbapenem-resistant isolates were most frequent in the Medicine Ward (26.32%) and Pediatric Ward (26.32%).Conclusion: Carbapenem-resistant organisms are increasingly prevalent in tertiary care hospitals, posing a significant therapeutic challenge. Regular hospital based surveillance, coupled with stringent infection control measures and rational antimicrobial use, is crucial to curb the spread of these resistant pathogens and improve patient outcomes.IAHS Medical Journal Vol 8(2), December 2025; 29-34